2013
DOI: 10.4274/tjem.2058
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Quality of Life Among Adult Turkish Patients with Type 1 Diabetes Mellitus

Abstract: Purpose: The aim of this study was to investigate quality of life, depression, and anxiety and to determine the variables of illness and sociodemographic features among type 1 diabetic patients and to compare with control subjects. Material and Method: The Short Form-36 (SF-36) questionnaire for measuring quality of life (QOL), The Beck Depression Inventory, and the State-Trait Anxiety Inventory (STAI) were administered to 58 diabetic patients and 58 control subject (Mean age: 31.9±8.5 and 31.8±7.4 years, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The EQ-5D index, EQ-5D-VAS index, Beck-depression and Beckanxiety scales' scores were reported from previous studies in the Turkish population from various diseases. These scores were defined as a 0.91, 87, 8, 6 for the EQ-5D, EQ-5D-VAS, Beck-depression and Beck-anxiety scales, respectively [39][40][41]. The different scale scores between the present study and previous published papers in the Turkish population confirm our hypothesis.…”
Section: -Tse Was Correlated Significantly and Positively Withsupporting
confidence: 81%
“…The EQ-5D index, EQ-5D-VAS index, Beck-depression and Beckanxiety scales' scores were reported from previous studies in the Turkish population from various diseases. These scores were defined as a 0.91, 87, 8, 6 for the EQ-5D, EQ-5D-VAS, Beck-depression and Beck-anxiety scales, respectively [39][40][41]. The different scale scores between the present study and previous published papers in the Turkish population confirm our hypothesis.…”
Section: -Tse Was Correlated Significantly and Positively Withsupporting
confidence: 81%
“…Johnson et al [27] found that T1DM was a reason for mental health screening. In addition to this, Atasoy et al [28] found that T1DM patients were prone to depression and anxiety, and their quality of life was worse. In these respects, closer monitoring is recommended.…”
Section: Discussionmentioning
confidence: 97%
“…Control is an even more complex issue for children and adolescents because it requires rationalizing the disease and consequently what can and cannot be done 2 . Therefore, patients diagnosed with chronic diseases such as DM are more likely to develop pathological forms of stress, anxiety, and depression and experience worse impact on quality of life 11,12 . Thus, depression and anxiety are associated with worse diabetes outcomes 5 …”
Section: Introductionmentioning
confidence: 99%